MANAJEMEN KONFLIK PADA SATUAN POLISI HUTAN REAKSI CEPAT (SPORC) BRIGADE BERUANG PROVINSI RIAU - Ryandi Martohonan Sibarani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Rise Of Case Criminal Forestry make the central government collaborate with Ministery of Forestry create the Forestry Police High-Speed Squad on 2005. Through this Organization, Forestry Problems can solve goodly, However, this organization Walk without no problems. From this problems it created conflicts. This conflicts causes Low-Coordination between Employee in Forestry Police High-Speed Squad (SPORC), during in the running main tasks and functions Forestry Police High-Speed Squad can’t solve the problems about Forestry Cases.The Purpose of this research is to know and analyze how the conflict management of the Forestry Police High-Speed Squad (SPORC) of Brigade Beruang Riau Province and also the factors which influencing that conflict Management. This research is using a research-qualitative method which it'd explore the problem ,Identify causes of factors, and Composing theory which it has basically investigate.The theory of this research is Theory of Conflict Management by Wirawan with Five Purposes of Conflict Managament , which is : Preventing from disturb to members organization, Understanding others and honoring differentials, Increasing Creativity, Increasing Decision through Opinions, and Facilitating realization of activity. And the technical analyze data using qualitative method.After the research it found that Conflict Management at Forestry Police High-Speed Squad (SPORC) Of Brigade Beruang Riau Province causes by Un-compatible Employee Placement, Un-Optimal Resources whom following the jobs, and Low-Coordination with Local Government.and the factors of incluiding conflict according to Forestry Minister Regulation Num.75 Year 2014 is : Physical Body, Discipline, Moral Integrity, and Technical ability enchancement.Keyword: Conflict Management, Forestry Police High-Speed Squad